Entrepreneurial manipulation with staged financing - Yung, Chris (Journal of Banking & Finance, 2019)
Finance is staged in entrepreneurial settings. It has been argued that staging has a drawback: entrepreneurs manipulate short-term appearances to keep funds flowing. In contrast, this paper finds that staging can lead to either more or less manipulation than non-staged finance. Finally, behavior in early rounds induces a kind of “manipulation persistence” so that total manipulation is path-dependent. The model makes predictions regarding crowdsourced finance, switching of VCs, and lifecycle issues in entrepreneurial finance.